PENGEMBANGAN BAHAN AJAR KETERAMPILAN BERBAHASA INDONESIA UNTUK SISWA SMA KELAS X - Haryati, Farida; Wiryotinoyo, Mujiyono; Sudaryono, Sudaryono (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
This article is based on research development that aims to produce teaching materials Indonesian language skill for 10th grade of high school students. Development design model used is based on the model of Dick and Carey (2005), which consists of ten steps. In general, based on data analysis showed that the quality of teaching materials Indonesian language skill for high school student of 10th grade semester 1 at the level of either spouse. Thus, it is recommended that the development of this product can be used as teaching materials in the senior high school education unit. Keyword: teaching materials and Indonesian language skill